ANALYSIS OF POSSIBILITIES TO PRESENT FORMALLY THE ELEMENTS OF VIRTUAL EDUCATIONAL SPACE - Morozova, О.; Морозова, О. І.; Морозова, О. И. (Харьковский национальный автомобильно-дорожный университет, 2017)
For formal representation of virtual educational space elements, the paper considers the topology methods, in particularly the methods for categories and functors theory, allowing for solving semistructured and indeterminate problems and reflecting their results at the high level of abstraction. The conducted analysis shows the virtual educational space as a generalized scheme, including an associative connection of the site of departments and general education schools.
АНАЛІЗ МОЖЛИВОСТЕЙ ФОРМАЛЬНОГО ПОДАННЯ ЕЛЕМЕНТІВ ВІРТУАЛЬНОГО ОСВІТНЬОГО ПРОСТОРУ
АНАЛИЗ ВОЗМОЖНОСТЕЙ ФОРМАЛЬНОГО ПРЕДСТАВЛЕНИЯ ЭЛЕМЕНТОВ ВИРТУАЛЬНОГО ОБРАЗОВАТЕЛЬНОГО ПРОСТРАНСТВА
Keywords: category theory; generalized scheme; colleges; schools; educational space; hyperlinks; WEB-sites; portals; віртуальний освітній простір; WEB-технології; освіта; навчання; формалізація; виртуальное образовательное пространство; WEB-технологии; образование; обучение; формализация; 004.89:378.4